Strong and Weak Forms of Î¼-Kc-Spaces - Nadhim, Nadia A.; Ali, Haider J.; Majeed, Rasha N. (Iraqi Journal of Science, 2020)
In this paper, we provide some types of - -spaces, namely, - ( )- (respectively, - ( )- , - ( )- and - ( )-) spaces for minimal structure spaces which are denoted by ( -spaces). Some properties and examples are given.The relationships between a number of types of - -spaces and the other existing types of weaker and stronger forms of -spaces are investigated. Finally, new types of open (respectively, closed) functions of -spaces are introduced and some of their properties are studied.